Case study: Comprehensive rehabilitation program after tumor resection of the proximal humerus and postresectional total shoulder joint arthroplasty - Szczypiór-Piasecka, Karina; Szwedowicz, Weronika; Mińko, Alicja; Antczak, Krzysztof; Orłowska, Aleksandra (Journal of Education, Health and Sport, 2021)
Bone sarcomas are malignant neoplasms that occur quite rarely. In all European countries, bone sarcoma accounts for less than 0.4% of reported malignancies. Bone sarcomas constitute a diverse group of neoplasms of mesenchymal origin. The current classification of bone sarcoma into histological subtypes is based on the origin of the given cells that constitute the bone components. The method of treatment of low-histological sarcomas is surgical removal of the tumor, but more than 70% of cases require combined treatment consisting of surgery and pre- and postoperative chemotherapy due to high histological malignancy. [1-3] The aim of this work is to present the program of comprehensive rehabilitation of the patient N.E. after resection of the tumor in the proximal part of the right humerus due to extensive metastasis of clear cell kidney cancer and the insertion of a MUTARS humerus implant. Male N. E., 62 years of age, after clear cell carcinoma (G2) of the left kidney after NSS (2010), was admitted to the surgery department on April 18, 16 due to pain in the upper abdomen and left shoulder. Post-hospital rehabilitation was performed four months after the surgery. Its main goal was to restore the maximum physical fitness possible for the patient after the arthroplasty of the shoulder joint. It mainly involved exercises to strengthen the muscle strength of the shoulder girdle, proprioception training, stabilization and preparation of the patient to perform self-service activities and return to professional activity [4,5].